74‐4: High‐image‐quality Transparent Display based on AMOLED with Cholesteric Liquid Crystal Back‐panel. Issue 1 (30th May 2018) - Li, Cheng-Chang; Tseng, Heng-Yi; Liao, Hung-Chia; Chen, Han-Ming; Hsieh, Ting; Lin, Sin-An; Jau, Hung-Chang; Wu, Yu-Ching; Ya-Ling, Hsu; Hsu, Wen-Hao; Lin, Tsung-Hsien
Abstract : The image quality of the transparent AMOLED, which is the most potential candidate of next generation technology, is highly dependent on the surroundings. In this work, the concept of high‐image‐quality transparent display based on AMOLED with a desirable liquid crystal shutter back‐panel is demonstrated.